Hubungan Pengaruh Fluktuasi Tinggi Muka Air dan Zat Pencemar Pada Saluran Bagian Tengah Dari Panjang Saluran Drainase Primer IV Kota Palangka Raya Dengan Outlet Di Sungai Kahayan - ARIFIN, SYAIFUL (INFO-TEKNIK, 2024)
Central Kalimantan has an area with a beautiful distribution of watersheds and abundant river products. Palangka Raya City is one of the watersheds included in it. Palangka Raya City has two rivers as estuaries for primary drainage channels, namely the Kahayan River and the Sebangau River. The Kahayan River is the final estuary of the primary drainage channels in the city of Palangka Raya, one of which is the IV primary drainage channel. This IV primary drainage channel is one of the primary drainage channels which contaminates the Kahayan River, which is its estuary. Contamination of contaminants from the primary drainage channel comes from domestic waste from residential communities living in the area. It is estimated that these pollutant materials will contaminate the water of the Kahayan River; thus, the need for research. In this study, the flow velocity and water level at a certain channel cross section were measured, then the water discharge was calculated, and several water samples taken from the middle of the IV primary drainage channel were tested for several parameters, namely BOD, COD, TSS, Ammonia, Oil-fat and Detergent. The results of the study showed that several test parameters had passed the predetermined class quality standard thresholds including BOD, Ammonia and Detergent so that they contributed to contaminating the Kahayan River. There are several parameters with a significant correlation between fluctuations in the water level and the value of the water discharge as indicated by the R-Square value > 0.67.